Hubungan Pengetahuan Orangtua tentang Perkembangan Bahasa dengan Kemampuan Bahasa Reseptif pada Autism Spectrum Disorder (ASD) di Pusat Layanan Disabilitas dan Pendidikan Inklusif Kota Surakarta - El Madina, Sofia; Susanti, Nadya (Jurnal Terapi Wicara dan Bahasa, 2023)
Background: Parents' knowledge of language development is one of the factors that influence children's language skills. Parents' knowledge needs to be increased by knowing the development of each language in each period of life, so that children will get their right to care, especially in language development which will determine their next life. Objectives: Describe the knowledge of parents about language development, describe the receptive language skills in children with Autism Spectrum Disorder (ASD) and to analyze the relationship between knowledge of parents about language development and receptive language skills in children with Autism Spectrum Disorder at Pusat Layanan Disabilitas dan Pendidikan Inklusif Kota Surakarta. Method: The type of research used is quantitative research with a cross sectional design. The sampling technique used purposive sampling with the number of respondents as many as 30 respondents. The statistical test used in this study is the Spearman’s rho. Results: The Spearman's rho test results, the results obtained were a ρ value of 0.016 or a ρ value <0.05, had a correlation coefficient (r) of 0.435 which was in the medium category, and had a unidirectional correlation direction. Conclusion: There is a positive correlation or relationship and moderate category between parental knowledge about language development with a ρ value of 0.016 and a correlation coefficient (r) of 0.435 on Autism Spectrum Disorder (ASD) receptive language skills. Keywords: Parental Knowledge, Receptive Language Skills, Autism Spectrum Disorder (ASD).